CONTAMINAÇÃO DE EQUIPAMENTOS E SUPERFÍCIES NA ÁREA DE TRABALHO DE ANESTESIA DA SALA DE OPERAÇÃO - Carlos Eduardo Macedo (2022)
The contaminated healthcare environment, including perioperative areas, plays an important role in the transmission of pathogens. Patients undergoing general anesthesia with Invasive Mechanical Ventilation (IMV) have variable health conditions, and contamination of the respiratory circuit and the medication preparation surface of the anesthesia machine can increase the risk of cross-infection. This study aimed to evaluate the contamination of the anesthetic medication preparation surface and of the respiratory circuit and of devices used in general anesthesia with assisted mechanical ventilation. The research took place in two phases, the first of which was to collect microbiological samples from the distal and proximal portions of the inspiratory and expiratory branches, from the canister of the respiratory circuit and from the surface of the anesthetic medication area. For each breathing circuit analyzed, three granules of soda lime were collected. In the second step, the collected material was seeded in blood agar, chocolate agar, MacConkey agar and Cled agar, in order to verify the growth and isolation of microorganisms. The observation of the plates was stipulated at the following time intervals: 12h, 24h, 36h, 48h and 60h. Eighty-two circuits/surfaces were collected, totaling 328 microbiological samples for analysis. Our findings point to the growth of the main microorganisms of pathogenic importance at different incubation times and sample collection sites (E. coli, Enterococcus spp.; Klebsiella spp.; Enterobacter spp.; Staphylococcus aureus; Proteus spp.; Pseudomonas spp.; Streptococcu pneumoniae; Streptococcus pyogenes; Enterococcus faecalis and Neisseria gonorrhoeae). In the Cled agar culture medium, there was a significant association between the growth times of the microorganisms in relation to the place where the samples were collected (P>0.05). In the other culture media, the sample collection location did not significantly influence the growth times of microorganisms (P>0.05). Of the total of 82 samples collected, only nine showed no fungal growth, most of them from the genus Candida spp. The results point to inadequate disinfection of the inspiratory and expiratory branches, and/or inadequate handling and internal storage of reprocessed products. Surface contamination of the anesthetic medication area (prior to preparation) is of concern and highlights the importance of cleaning and disinfecting high-touch surfaces in the anesthesia care and anesthesia work area between operating room uses with a disinfectant. approved hospital.